Numerical Distribution Functions for Unit Root and Cointegration Tests - James G. MacKinnon (Queen's University, Department of Economics, 1995)
This paper employs response surface regressions based on simulation experiments to calculate distribution functions for some well-known unit root and cointegration test statistics. The principal contributions of the paper are a set of data files that contain estimated response surface coefficients and a computer program for utilizing them. This program, which is freely available via the Internet, can easily be used to calculate both asymptotic and finite-sample critical values and P values for any of the tests. Graphs of some of the tabulated distribution functions are provided. There is also an empirical example.
Keywords: C22; 330; unit root tests; Dickey-Fuller tests; cointegration tests; Engle-Granger test; response surfaces; critical values; approximate P values; simulation methods